Model Participatory Rural Appraisal (PRA) Melalui Pemberdayaan Masyarakat Berbasis UMKM Di Kelurahan Ngronggo Kecamatan Kota Kediri - Toto Ardianto (Otonomi, 2023)
The process of community empowerment is an effort to help the community to develop their abilities independently. Through the Participatory Rural Appraisal (PRA) model as a guide in community empowerment based on Micro, Small and Medium Enterprises (MSMEs) in the Ngronggo Village. This model is carried out to find out the process of community empowerment in MSME activities in the Ngronggo Village which aims to optimize the welfare of the perpetrators. The research approach used is a qualitative approach with descriptive analysis techniques. Data collection techniques are carried out through observation, interviews, and documentation. The results of the research, namely: Ngronggo Village participates in assisting the community starting from exploring the potential of MSMEs, mapping community characteristics, determining strategies for optimizing production processes, marketing, building networks and coordination with relevant stakeholders as well as appropriate and complete permits needed for the products produced and evaluate the implementation on a regular basis together with the Kelurahan Social Institution. The development and capacity building of each element involved in the MSME sector is carried out continuously by participating in training and efforts to acquire capital for business development